2020 Clinical Engineers Salary Survey. Issue 4 (October 2021) - Manzoli, Michele
Abstract : Given the low number of Clinical Engineering professionals in the country, it is often difficult for healthcare organizations' human resources departments to determine appropriate salary ranges. This work aims at providing more visibility around actual salaries for specific Clinical Engineering positions in different geographic areas. More than 100 responses were received and analyzed, taking into consideration cost of living and seniority associated to each data point. Starting salaries were obtained for each position, allowing the reader to calculate—adjusting for tenure and local cost of living—their personal salary estimate. A larger number of participants in future surveys will determine more accurate results.